217k views
0 votes
Solving Quadratic Equations by completing the square:

z^2 - 3z - 5 = 0

2 Answers

4 votes

Answer:
z_1=4.19\\\\z_2=-1.19

Explanation:

Add 5 to both sides of the equation:


z^2 - 3z - 5 +5= 0+5\\\\z^2 - 3z = 5

Divide the coefficient of
z by two and square it:


((b)/(2))^2= ((3)/(2))^2

Add it to both sides of the equation:


z^(2) -3z+ ((3)/(2))^2=5+ ((3)/(2))^2

Then, simplifying:


(z- (3)/(2))^2=(29)/(4)

Apply square root to both sides and solve for "z":


\sqrt{(z- (3)/(2))^2}=\±\sqrt{(29)/(4) }\\\\z=\±\sqrt{(29)/(4)}+ (3)/(2)\\\\z_1=4.19\\\\z_2=-1.19

User Thevikasdube
by
4.7k points
7 votes

Answer:


(z-(3)/(2) )^2-(29)/(4)

Explanation:

We are given the following quadratic equation by completing the square:


z^2 - 3z - 5 = 0

Rewriting the equation in the form
x^2+2ax+a^2 to get:


z^2 - 3z - 5+(-(3)/(2) )^2-(-(3)/(2) )^2


z^2-3z+(-(3)/(2) )^2=(z-(3)/(2) )^2

Completing the square to get:


( z - \frac{ 3 } { 2 } )^ 2 - 5 - ( - \frac { 3 } { 2 } ) ^ 2


(z-(3)/(2) )^2-(29)/(4)

User Raees Iqbal
by
4.8k points